2019
DOI: 10.1088/1751-8121/ab3079
|View full text |Cite
|
Sign up to set email alerts
|

Mean field theory of jamming of nonspherical particles

Abstract: Recent computer simulations have uncovered the striking difference between the jamming transition of spherical and non-spherical particles. While systems of spherical particles are isostatic at the jamming point, systems of nonspherical particles are not: the contact number and shear modulus of the former exhibit a square root singularity near jamming, while those of the latter are linearly proportional to the distance from jamming. Furthermore, while our theoretical understanding of jamming of spherical parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…For small n, z J increases upon increasing μ; see the data for n ¼ 10. Since μ=n represents the deviation from disks, this behavior is qualitatively similar to that observed in convex-shaped particles [5,[32][33][34][35][36][37][38]. Contrarily, for large n, z J decreases with μ [41].…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…For small n, z J increases upon increasing μ; see the data for n ¼ 10. Since μ=n represents the deviation from disks, this behavior is qualitatively similar to that observed in convex-shaped particles [5,[32][33][34][35][36][37][38]. Contrarily, for large n, z J decreases with μ [41].…”
mentioning
confidence: 53%
“…In this work, we construct a new model to take into account the effect of surface roughness by means of a perturbative expansion around the reference case of spherical disks. By performing numerical simulations, we show that, for a smooth surface, z J of the model increases upon increasing asphericity, suggesting that a small deviation from perfect disks plays a similar role to the asphericity of convexshaped particles [5,[32][33][34][35][36][37][38]. Contrarily, for a rough surface, z J decreases upon increasing asphericity, as for frictional particles.…”
mentioning
confidence: 82%
“…Note that the same equation of eq. (42) holds exactly in the case of mean-field model of nonspherical particles [5,9] and the spherical particles slightly above the jamming transition point, where δz ∼ p 1/2 [23]. For the force distribution P (f ), one can apply a similar argument, and it has been shown that…”
Section: General Scaling Form Of the Distribution Functions Near Isosmentioning
confidence: 85%
“…Using the previous theoretical analysis [5,9], one can interpret the above results as follows: (i) The lowest band corresponds to the zero modes stabilized by the positive part of the pre-stress. As the pre-stress scales as k R ∼ p∆, eq.…”
Section: Characteristic Frequenciesmentioning
confidence: 88%
“…Then one wants to minimize the volume of the phase space of the vector x, for example by minimizing |x| 2 , such that there is a configuration that satisfies all constraints. This problem is related to the packing problem and has been analyzed in [2][3][4][5][6][7][8][9], see also [10] for a review with the corresponding connection to deep learning.…”
Section: Introductionmentioning
confidence: 99%